2016
DOI: 10.1177/0049475515627235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypothyroidism in rheumatoid arthritis and its correlation with disease activity

Abstract: Thyroid function test should be included in clinical evaluation of RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
5
16
0
Order By: Relevance
“…[ 10 ] Our results also confirmed that there was no association between presence of thyroid disorders in RA patients and age, and also IgM RF; however, we think that small difference between our results and Shiroky et al's results was caused by methodological or laboratory analysis differences. Our results were in line with a recent study by Joshi et al [ 24 ] and illustrated that there was a significant correlation between disease activity (at the time of diagnosis) and thyroid disorders among RA patients. A population-based, case-control study (1998 adult cases vs 2252 controls) by Bengtsson et al [ 25 ] revealed that patients treated with thyroxin (hypothyroidism) were at double risk of both anti-CCP negative (odds ratio [OR] 2.1, 95% confidence interval [CI] 1.5–3.1) and anti-CCP positive (OR 1.9, 95% CI 1.4–2.6) RA.…”
Section: Discussionsupporting
confidence: 94%
“…[ 10 ] Our results also confirmed that there was no association between presence of thyroid disorders in RA patients and age, and also IgM RF; however, we think that small difference between our results and Shiroky et al's results was caused by methodological or laboratory analysis differences. Our results were in line with a recent study by Joshi et al [ 24 ] and illustrated that there was a significant correlation between disease activity (at the time of diagnosis) and thyroid disorders among RA patients. A population-based, case-control study (1998 adult cases vs 2252 controls) by Bengtsson et al [ 25 ] revealed that patients treated with thyroxin (hypothyroidism) were at double risk of both anti-CCP negative (odds ratio [OR] 2.1, 95% confidence interval [CI] 1.5–3.1) and anti-CCP positive (OR 1.9, 95% CI 1.4–2.6) RA.…”
Section: Discussionsupporting
confidence: 94%
“…16 we measured the disease activity using DAS-ESR score and VAS and we found significant correlation between serum levels of TSH and disease activity parameters (ESR and DAS-28), as did the study by Elattar et al 3 The comparison between two groups created in patients based on presence or absence of thyroid dysfunction showed disease activity parameters such as the visual analogue scale for pain, patients' global health assessment score, tender joint count, DAS-28 and ESR were significantly higher in patients of thyroid dysfunction group as compared to patients of normal thyroid functions. Swollen joint count was also higher in first group but this difference was not statistically significant the results where correlating with study done by Prakash Joshi et al 17…”
Section: Discussionsupporting
confidence: 83%
“…It has been estimated that onethird of the genetic risk for RA resides within this locus. Most, but probably not all, of this risk is associated with allelic variation in the HLA-DRB1 gene, which encodes the MHC II β-chain molecule [4] thus common genetic predisposition between AITD and RA could be one of the reason for there co existence in many patients.In this study prevalence of rheumatoid arthritis among 200 hypothyroid patient was found to be 24.5% including 18.5% of females and 6% males which is supported by study conducted by other authors too [5,6] Osteoarthritis (OA) isn't caused by immune system issues. Emerging evidence has identified genetic mutations that confer a high risk of OA, the best replicated is a polymorphism within the growth differentiation factor 5 gene.…”
Section: Introductionsupporting
confidence: 69%